Multiomics of yaks reveals significant contribution of microbiome into host metabolism - Shuli Yang; Jieyi Zheng; Huaming Mao; Paramintra Vinitchaikul; Dongwang Wu; Jianmin Chai (npj Biofilms and Microbiomes)
Abstract An intensive feeding system might improve the production cycle of yaks. However, how intensive feeding system contributes to yak growth is unclear. Here, multi-omics, including rumen metagenomics, rumen and plasma metabolomics, were performed to classify the regulatory mechanisms of intensive feeding system on yaks. Increased growth performance were observed. Rumen metagenomics revealed that Clostridium, Methanobrevibacter, Piromyces and Anaeromyces increased in the intensively fed yaks, contributing to amino acid and carbohydrate metabolism. The grazing yaks had more cellulolytic microbes. These microbiomes were correlated with the pathways of “Alanine aspartate and glutamate metabolism” and “Pyruvate metabolism”. Intensive feeding increased methane degradation functions, while grazing yaks had higher methyl metabolites associated with methane production. These rumen microbiomes and their metabolites resulted in changes in plasma metabolome, finally influencing yaks’ growth. Thus, an intensive feeding system altered the rumen microbiome and metabolism as well as host metabolism, resulting in improvements of yak growth.